Updates in vascular access: percutaneous endovascular dialysis fistulas. (2nd March 2019) - Inston, Nicholas; Jones, Robert
Abstract : For patients who require haemodialysis as their modality of renal replacement therapy, the timely creation of definitive vascular access is one of the most important factors in their care. In this article, Nicholas Inston and Robert Jones explore developments in fistula devices in recent years, and review the developing evidence base surrounding them. Patient selection and patient benefits are discussed